Challenges of Teaching Entrepreneurship Component of Economics and Management Sciences in South African Schools - Mbatha, Lungelo Sithuthuko; Ndovela, Sithembele Goodman (E-Journal of Humanities, Art and Social Sciences (Online), 2024)
Economic and Management Sciences (EMS) is one of the fields of study in the South African school curriculum. It covers three components namely, financial literacy, economy and Entrepreneurship. This article presents the findings on the challenges of the teaching of the Entrepreneurship component of the EMS. Piaget’s (1967) Constructivism theory was employed as a theoretical lens to understand the challenges of the teaching of the Entrepreneurship component of EMS. The researchers used an interpretivism-qualitative approach grounded in the case study as a research methodology. The sample of five EMS teachers who teach EMS in five different schools in the uThukela education district in KwaZulu-Natal province. The data was collected through face-to-face semi-structured interviews and it was analysed using thematic analysis. The following findings were revealed: a shortage of qualified EMS teachers, insufficient teaching resources, limited understanding of the language of teaching and learning and minimal support from EMS subject advisors. It is recommended that the Department of Education must employ qualified EMS teachers and also offer workshops focusing on content and pedagogical knowledge of the EMS. It could be concluded that there are challenges in relation to the teaching Entrepreneurship component. The study contributes with theory and practice regarding the teaching of Entrepreneurship. Keywords: Entrepreneurship, Economic and Management Sciences, constructivism